Characteristics of the spinopelvic parameters of patients with sacroiliac joint pain - Tonosu, Juichi (Sci Rep, 2021)
To evaluate the characteristics of the spinopelvic parameters on radiography in patients with sacroiliac joint pain (SIJP). Two hundred fifty patients were included and divided into the SIJP group (those diagnosed with SIJP based on physical findings and response to analgesic periarticular injections; n = 53) and the non-SIJP group (those with low back pain [LBP] because of other reasons; n = 197). We compared their demographic characteristics and spinopelvic parameters using radiography. All differences found in the patients’ demographic characteristics and spinopelvic parameters were analyzed. More female participants experienced SIJP than male participants (P = 0.0179). Univariate analyses revealed significant differences in pelvic incidence (PI) (P = 0.0122), sacral slope (SS) (P = 0.0034), and lumbar lordosis (LL) (P = 0.0078) between the groups. The detection powers for PI, SS, and LL were 0.71, 0.84, and 0.66, respectively. Logistic regression analyses, after adjustment for age and sex, revealed significant differences in PI (P = 0.0308) and SS (P = 0.0153) between the groups, with odds ratios of 1.03 and 1.05, respectively. More female participants experienced SIJP than male participants. Higher PI and SS values were related to SIJP among LBP patients.